beta-NMR of Palladium foil - Parolin, T; Salman, Z; Chakhalian, J; Wang, D; Keeler, T; Hossain, M; Kiefl, R; Chow, K; Morris, G; Miller, R; MacFarlane, W (2006)
Beta-detected NMR (beta-NMR) of low-energy implanted Li-8(+) was studied in metallic palladium. The resonance was found to have a large negative shift with respect to the reference signal in the cubic insulator MgO. This shift exhibited significant temperature dependence on cooling below room temperature, approximately proportionate to the temperature-dependent spin susceptibility of pure Pd. Thus it is tentatively attributed to a Knight shift (K) caused by a large negative hyperfine coupling; a phenomenon common in transition metal ions, but not in alkalis. However, the spin-lattice relaxation of Li-8 is much slower than expected from the Korringa law for such a large K. We compare results from samples of very different thicknesses: 12.5 mu m foil and a 100 nm thin film. (c) 2005 Elsevier B.V. All rights reserved.